Insurance Status Predicts Periprosthetic Joint Infection after Total Hip Arthroplasty - Thomas, Jeremiah; Anil, Utkarsh; Schmicker, Thomas; Lin, Charles C.; Aggarwal, Vinay K.; Schwarzkopf, Ran (The Journal of Hip Surgery, 2024)
Periprosthetic joint infection (PJI) is one of the most severe complications following total hip arthroplasty (THA), and identifying factors associated with PJI is vital for preoperative risk stratification. The aim of this study was to compare risk of PJI after THA across insurance payers using a statewide health data registry. A retrospective review was conducted querying the New York Statewide Planning and Research Cooperative System for all patients undergoing elective unilateral primary THA using International Classification of Diseases (ICD)-9 and ICD-10 procedure codes. Patients were stratified into groups based on their insurance provider as private payer, Medicare, Medicaid, or worker's compensation. Demographics, hospital clinical data, complications, PJI rates, and mortality rates were collected. PJI rates were significantly different between groups at both 3 (p < 0.001) and 12 months (p < 0.001) postoperatively, highest at both time points in the Medicaid group (3 months: 1.3%; 12 months: 1.8%). Log-rank test demonstrated increased cumulative PJI rates in the worker's compensation and Medicaid groups up to 108 months postoperatively (p < 0.001). Multivariate Cox proportional hazard regression, adjusted for demographics, found that Medicaid insurance was associated with 1.4 times increased risk for PJI relative to Medicare (hazard ratio:1.39; 95% confidence interval [1.19, 1.62]; p < 0.001). These results suggest patients undergoing THA covered by Medicaid are at increased risk for PJI compared with patients covered by other insurance payers. Surgeons should recognize this patient population is at an increased risk for PJI, and compensation policies for treating patients covered by Medicaid should reflect the increased complication rate associated with this population.
Keywords: insurance; periprosthetic joint infection; total hip arthroplasty; Medicaid